2012
DOI: 10.1016/j.wneu.2011.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Brain Tumors in Infants Younger than Six Months of Age and Review of the Literature

Abstract: Object Brain tumors are rare in infants under 6-months of age. These tumors can be challenging to treat surgically. We analyzed a modern series of patients treated by a multidisciplinary team at a tertiary care center and performed a literature review of this unique population. Methods Retrospective clinical data was collected for patients surgically treated for intracranial mass lesions at The Children’s Hospital of Philadelphia from 1998 to 2007. Dermoid cysts and other skull-based lesions were excluded fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 59 publications
1
36
0
1
Order By: Relevance
“…This could be due to the noninclusion of subjects with extracranial benign teratoma. A main problem of this tumor is the surgical aspect due to the importance of the tumor with probably a high mortality . We reported a poor survival for CNS tumors.…”
Section: Discussionmentioning
confidence: 77%
“…This could be due to the noninclusion of subjects with extracranial benign teratoma. A main problem of this tumor is the surgical aspect due to the importance of the tumor with probably a high mortality . We reported a poor survival for CNS tumors.…”
Section: Discussionmentioning
confidence: 77%
“…Brain MRI 1 month after surgery demonstrated rapid growth of the hypothalamic mass as well as of the pial [4]. It is difficult in infantile cerebral neoplasms to predict tumor histology and grading on the basis of the preoperative imaging, and surgical resection or biopsy to establish a diagnosis has been recommended [12,21]. Surgical resection has also been favored for treatment of DIA, and good quality of life can be achieved on long-term follow-up in patients with a single mass [7,21].…”
Section: Discussionmentioning
confidence: 99%
“…[1] Brain tumors are quite uncommon in infants, especially below 6 months of age and when they occur have a dismal course. [2] The sites of occurrence, histopathology, and presentation differ considerably in infants when compared with other age groups. Teratomas are the most common congenital tumors with GBM accounting for 2-9%.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Lang et al ., surgical treatment outcomes were assessed in infants younger than 6 months with brain tumors and it was concluded that tumors of different histopathology had a variable but definite impact on the quality of life with residual neurological sequelae post surgery. [2]…”
Section: Discussionmentioning
confidence: 99%